Precipitation-driven restructuring of rhizosphere microbiota enhances alpine plant adaptation - Chen, Chao; Xu, Dafeng; Jiang, Benli; Lu, Xianyong; Yu, Chun; Wang, Yujiao; Wang, Hongjuan; Li, Jingna; Zhu, Jiabao (Frontiers in Plant Science, 2025)
IntroductionClimate-driven precipitation changes are increasingly threatening alpine ecosystems, yet the adaptive responses of soil microbiomes to rainfall variability remain poorly characterized. This knowledge gaphinders our ability to predict ecosystem resilience under future climate scenarios.MethodsWe combined metagenomic sequencing with detailed physicochemical analyses to examine how natural precipitation events reshape the microbial communities in both rhizosphere and bulk soils associated with Poa alpigena in the alpine sandy ecosystems of Qinghai Lake.ResultsRainfall significantly reduced bacterial alpha diversity, particularly in bulk soils, and triggered a compositional shift from drought-resistant taxa (e.g., Geobacter, Pseudomonas) to moisture-adapted genera (e.g., Azospirillum, Methylobacterium). Actinobacteria remained consistently dominant (31.56-34.62%), while Proteobacteria abundance decreased markedly in the rhizosphere post-rainfall. Metabolic reconstruction revealed a transition from pre-rainfall carbohydrate catabolism to post-rainfall anaerobic energy production and carbon fixation pathways. The rhizosphere microbiome uniquely displayed drought-induced biofilm formation and rainfall-enhanced branched-chain amino acid metabolism. Soil moisture and total carbon were identified as primary drivers of microbial restructuring in bulk soils, whereas root exudates conferred stability to rhizosphere communities against hydrological fluctuations.DiscussionThese results elucidate microbiome-mediated adaptive strategies to precipitation changes in alpine sandy ecosystems, highlighting the critical buffering role of plant-microbe interactions. The study provides a mechanistic basis for predicting and restoring climatevulnerable wetlands under increasingly variable hydrological regimes.